Inflation of tumor mutation burden by tumor-only sequencing in under-represented groups - Yan W. Asmann (Nature Portfolio, 2021)
Abstract With the recent FDA approval of tumor mutational burden-high (TMB-H) status as a biomarker for treatment with a PD-1 inhibitor regardless of tumor type, accurate assessment of patient-specific TMB is more critical now more than ever. Using paired tumor and germline exome sequencing data from 701 patients newly diagnosed with multiple myeloma, including 575 self-reported White patients and 126 self-reported Black patients, we observed that compared to the gold standard of filtering germline variants with patient-paired germline sequencing data, TMB estimates were significantly higher in both Black and White patients when using public databases for filtering non-somatic mutations; however, TMB was more significantly inflated in Black patients compared to White patients. TMB as a biomarker for patient selection to receive immune checkpoint inhibitors (ICIs) therapy without patient-paired germline sequencing may introduce racial bias due to the under-representation of minority groups in public databases.